Dajanje kortikosteroidov ženskam v nosečnostih, ki se končajo s prezgodnjim porodom - Pirih, Alenka (Medicinski razgledi, 2005)
Preterm delivery is associated with neonatal mortality, severe neonatal morbidity with long-term consequences, and disturbances in neurologic development. However, when prevention of preterm delivery is impossible, preventative administration of corticosteroids at least 24 hours prior to preterm delivery has been proved to reduce neonatal mortality and morbidity. Our aim was to find out why only 38.6% of children born between 28. 0/7 and 32. 6/7 weeks of gestation at the Ljubljana Maternity Hospital during the year2000 received antenatal corticosteroids. An attempt was made to evaluate the standard values (sensitivity, specificity, and positive and negative predictive values) of the test that detects the phosphorylated form of insulingrowth factor binding protein type 1 (phIGFBP-1) in the cervical fluid for prediction of preterm delivery, and to increase its usage. Our aim was also to draw up recommendations on how to increase the number of pregnant women with a high risk of preterm delivery that are given corticosteroids. It was expected that over 38.6% of pregnant women who delivered their babies between 28. 0/7 and 32. 6/7 weeks of gestation would have been treated with corticosteroids. However, this was not indicated in the delivery protocol. Thedesire was to evaluate standard values of the test for detecting phIGFBP-1.It is expected that our recomendations will increase the number of pregnant women at high risk of preterm delivery to be treated with corticosteroids. In the retrospective part, perinatal data were analyzed on women who delivered between 22. 0/7 and 33. 6/7 week of gestation in the year 2000 at the Ljubljana Maternity Hospital. It was analyzed how many were given corticosteroids, whether they received them at least 24 hours prior to delivery and whether this was marked in delivery protocol. (Abstract truncatedat 2000 characters)
Keywords: Dejavniki tveganja; Labor, Premature; Gestacijska starost; Risk Factors; Adrenal Cortex Hormones; Inzulin-podobni, rastni-faktor, vezalna beljakovina 1; Kortikosteroidi; Insulin-Like Growth-Factor Binding Protein 1; Porod prezgodnji; Gestational Age; childbirth; porod; prezgodnji porod; novorojenčki; nosečnice; preventivna medicina